2013
DOI: 10.1073/pnas.1304801110
|View full text |Cite
|
Sign up to set email alerts
|

Molecular determinants of PI3Kγ-mediated activation downstream of G-protein–coupled receptors (GPCRs)

Abstract: Phosphoinositide 3-kinase gamma (PI3Kγ) has profound roles downstream of G-protein-coupled receptors in inflammation, cardiac function, and tumor progression. To gain insight into how the enzyme's activity is shaped by association with its p101 adaptor subunit, lipid membranes, and Gβγ heterodimers, we mapped these regulatory interactions using hydrogen-deuterium exchange mass spectrometry. We identify residues in both the p110γ and p101 subunits that contribute critical interactions with Gβγ heterodimers, lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
177
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(203 citation statements)
references
References 55 publications
19
177
0
Order By: Relevance
“…Rab5 was previously implicated as an effector for class IA PI3Kb 44 , although the nature of this interaction was not characterized. At a molecular level, the PI3K catalytic subunit p110g is traditionally recruited by binding directly to Ras, along with a class IB regulatory subunit, and the Gbg subunit of an activated GPCR complex 45 . We now confirm that Rab8a and PI3Kg bind directly to each other, using homology modelling and mutagenesis of critical residues.…”
Section: Discussionmentioning
confidence: 99%
“…Rab5 was previously implicated as an effector for class IA PI3Kb 44 , although the nature of this interaction was not characterized. At a molecular level, the PI3K catalytic subunit p110g is traditionally recruited by binding directly to Ras, along with a class IB regulatory subunit, and the Gbg subunit of an activated GPCR complex 45 . We now confirm that Rab8a and PI3Kg bind directly to each other, using homology modelling and mutagenesis of critical residues.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogen-deuterium exchange was essentially as described in ref. 30. For details of these and other biophysical methods, see SI Methods.…”
Section: Methodsmentioning
confidence: 99%
“…Exchange is stopped at various times by reducing the pH, the protein digested with pepsin, and the deuterium content of peptides determined by mass spectrometry (29). Because the rate of exchange depends strongly on tertiary structure and solvent accessibility, such studies can give information about binding or protein conformation, which are revealed by changes in the kinetics of deuterium incorporation into specific peptides (30,31). Fig.…”
Section: Significancementioning
confidence: 99%
“…HDX‐MS has also been used as a powerful tool to map out protein‐protein interfaces both in solution and on membrane surfaces 15, 16, 17, 18, 19, 20. Herein we describe an experimental approach to use HDX‐MS to define dynamic regions within a protein complex, in this case the type III phosphatidylinositol 4 kinase beta (PI4KIIIβ) in complex with the GTPase Rab11, and use this information to generate optimized constructs for X‐ray crystallography.…”
Section: Introductionmentioning
confidence: 99%